تقنيات السرد والنزوع التجريبي في القصة القصيرة العمانية ــ المجموعة القصصية كائناتي السردية للكاتبة ليلي لبلوشي أنموذجا ــ - بومعزة, نوال (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى محاول رصد أهمّ مظاهر التجريب القصصي، وتطوّر تقنيات السرد في القصة القصيرة العمانية، التي انفتحت على الكثير من الآليات السردية الجديدة كتوظيف تقنية أنسنة الأشياء، وحضور خطاب السخرية. وللوقوف عند هذه الاستنتاجات اتبعت تحليل نموذج قصصي ينتمي إلى القصة القصيرة العمانية المعاصرة حاول تحقيق التميز بتوظيف تقنيات سردية جديدة جعلت من المتن فضاء للنزوع التجريبي الذي ينشده كل كاتب. وقد قمت باستقراء النموذج بالاستعانة بمنجزات السرديات الحديث خاصة ما تعلق منها بتحليل تقنيات السرد والبحث عن خصائص الشكل الذي حتما أسهم في نقل قضايا الواقع بواسطة تفاعل الخطابات وتوظيف الرموز. This study aims to try to monitor the most important aspects of storytelling experimentation, and the development of narrative techniques in omani short story, which has opened up to many new narrative mechanisms such as the recruitment of the technique of humanizing things and attending the discourse of ridicule. To draw these conclusions, I followed the analysis of a story model that belonged to the contemporary short story of the blindness, which tried to achieve excellence by employing new narrative techniques that made the board a space for the experimental propensity that each writer desires. I extrapolated the model using the achievements of modern narratives, particularly by analysing narrative techniques and searching for the characteristics of the form that inevitably contributed to the transmission of reality issues through speech interaction and the use of symbols
مقال
Keywords: تقنيات ; السرد ; التجريب ; القصة ; العمانية ; التميز